The Effect of Internal Control on the Financial Performance of the North Gorontalo Regency Government - Yanti Aneta; Abdul Wahab Podungge (Iapa Proceedings Conference, 2021)
This study aims to determine and describe whether there is an influence of internal supervision on the financial performance of the North Gorontalo Regency Government. Design/Methodology/Approach: The sample involved 84 respondents of local government officials from the planning division, and those in charge of activities at all regional organizations in North Gorontalo District-Indonesia. This study used an explanatory method with a quantitative approach. Furthermore, the reflective model measurement used convergent and discriminant validity. In addition, the Partial Least Square-Structural Equation Modeling (PLS-SEM) technique was used as the data analysis. The results showed that Internal Control had a positive but not significant effect on the Government's Financial Performance of North Gorontalo Regency. The results of data analysis explain that the higher the Internal Control carried out by APIP, the significant value of the influence of the North Gorontalo Regency Government's Financial Performance, on the contrary, the lower the Internal Control carried out by APIP, the lower the significant value of the influence of the North Gorontalo Regency Government's budget performance. The supervision in question is the supervision carried out internally by the local government by the Government Internal Supervisory Apparatus (APIP), and is directly responsible to the regional head of the Regent/Deputy Regent. In carrying out its functions, APIP conducts independent assessments within the organizational unit based on the relevant authority, with the aim of knowing the entire process of activities starting from planning, implementation, programs and activities, until the evaluation of audit reviews, monitoring, and other supervisory activities on the implementation of tasks. and organizational functions.